The Development of Teachers' Potential Regarding Behavior Modification of Students with Special Education needs of Special Education Center: The Curriculum Development of Teachers' Potential Regarding Behavior Modification of Students with Special Education needs of Special Education Center - Chusak Siricheangpin, ชูศักดิ์ ศิริเชียงพิณ; Phanat Nakboon, พนัส นาคบุญ; Anucha Phoommisittiporn, อนุชา ภูมิสิทธิพร; Suwapatchara Changpinit , สุวพัชร์ ช่างพินิจ; Siriwimol Jai-ngam, ศิริวิมล ใจงาม (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The purpose of this study was three-fold: to study of problems and needs, to develop a curriculum and to compare the development of teachers' potential regarding behavior modification of students with special education needs of special education center. The subjects were 26 respondents, including 26 teachers in the regional special education center 7, Phitsanulok and Sukhothai special education center by using specific sampling. The study was conducted during the second semester in the academic year 2019. The main instruments included 1) a questionnaire form, 2) an evaluation form of teachers’knowledge, 3) a test and 4) interview. These main instruments were administered and then data were analyzed and presented by frequency analysis, percentage, mean, standard deviation and t - test. The results of this study revealed that A study of problems and needs the development of teachers' potential regarding behavior modification of students with special education needs of special education center, were as follows. Problem in workplace include behavioral problems of children with special needs (19.30%) and problem in managing stress and control emotions (17.80%). The need for the development of teachers' potential include behavior modification of children with special needs (19.30%) and stress management and emotional control techniques (19.30%) A development a curriculum the development of teachers' potential regarding behavior modification of students with special education needs of special education center, the knowledge and behavior modification of the teachers after the training session were higher than before the training at the significantly different level of 0.05 in all aspects. 3. The application of the knowledge in the development of teachers' potential regarding behavior modification of students with special education needs of special education center, there were no significant differences.